An Omnidirectional Antenna with Multi-taper Conformal Structure - Jiang, Zhaoneng; Sha, Yongxin; Xuan, Xiaofeng; Nie, Liying (Applied Computational Electromagnetics Society Journal (ACES), 2023)
In this paper, a wideband quadrangular pyramid conformal printed dipole antenna is designed, manufactured, and tested. The proposed antenna comprises four dipoles pointing in different directions and four pairs of parasitic patches. Each dipole and pair of parasitic patches are placed on one side of the pyramid. The simulated impedance bandwidth exceeds 26% (S11 ≤ −10 dB), with the conformal taper varied from 0∘ to 20∘. Omnidirectional radiation characteristics can be realized within the working bandwidth. The prototype of the proposed antenna with 10∘ taper is fabricated and measured. Moreover, the results show that the operating frequency band is 2.28-3.58 GHz in the S-band. The size of the fabricated antenna is 35 × 35 mm2. The conclusion is that the simulation and test results of the 10∘ taper antennas are highly consistent.